A new record of complete mitochondrial genome of Parantica aglea (Lepidoptera: Danainae) and its phylogeny. Issue 2 (2nd April 2020) - Li, Xiao-Dong; Wang, Yu-Qi; Rong, Wan-Tao; Liu, Xin-Yi; Li, Ran
Abstract: Parantica aglea (Lepidoptera: Nymphalidae: Danainae) was the type species of the genus Parantica . In this study, the complete mitochondrial genome (mitogenome) of P . aglea (GenBank accession No. MN938921) was sequenced using the polymerase chain reaction (PCR) method. Its mitogenome was a circular molecule of 15, 214 bp in length, containing 13 protein-coding genes, two ribosomal RNAs, 22 transfer RNAs, and one AT-rich region. The A + T content of the overall base composition of H-strand was 79.6%. All of the 13 protein-coding genes were begun with typical start codon ATN except COI using CGA. Four genes (COI, COII, ND4, and ND5) were ended with an incomplete stop codon (TA– or T––), and the remaining nine terminated with TAN. In the Bayesian inference (BI) phylogenetic tree, P. aglea was positioned near P. sita niphonica and P. s. sita within the genus Parantica .